Kettin, a large modular protein in the Z-disc of insect muscles. - Lakey, A (1993)
Z-discs of insect flight muscle contain a large protein of 500-700 kDa. Monoclonal antibodies label an epitope in the molecule at the Z-disc in Drosophila and Lethocerus (waterbug). A partial cDNA of 1.6 kb from the Drosophila gene has been cloned and sequenced. The corresponding amino acid sequence has a modular structure composed of four conserved repeats of 95 amino acids homologous to immunoglobulin C2 domains (called class II domains in muscle proteins), separated by less conserved linker sequences of 35 amino acids. An expressed class II domain with flanking linker sequences binds to actin and alpha-actinin but not to myosin. Single molecules of the protein would be large enough to span the Z-disc. We suggest that the protein acts as scaffolding in the Z-disc and we call the protein kettin. The Ca2+ activated protease, calpain, disrupts the Z-disc of striated muscle, releasing alpha-actinin intact. Calpain digests kettin to a series of peptides of between 30 and 170 kDa which are released from the myofibril. Digestion of kettin may cause disintegration of the Z-disc and alpha-actinin release which lead to disassembly of the myofibril.